Sarcina ventriculi in an Endoscopic Ultrasound-Guided Fine Needle Aspiration of a Perigastric Lymph Node with Metastatic Pancreatic Adenocarcinoma: A Carry-Through Contaminant Bacterial Microorganism from the Stomach - Bharat Nandakumar; Diva R. Salomao; Nicholas A. Boire; Audrey N. Schuetz; Charles D. Sturgis (Case Reports in Pathology)
Sarcina ventriculi is a rare gram-positive coccus increasingly reported in patients with a history of delayed gastric emptying or gastric outlet obstruction and is sometimes seen in association with emphysematous gastritis and perforation. We report a case of a 67-year-old male who presented with epigastric pain. CT imaging and cholangiopancreatography were concerning for pancreatic neoplasia. Upper endoscopic ultrasound-guided fine needle aspiration cytology of a perigastric lymph node confirmed metastatic adenocarcinoma of pancreatic origin, and cocci arranged in a tetrad fashions characteristic of Sarcina ventriculi were noted. To our knowledge, this is the first reported case of Sarcina ventriculi in an FNA of metastatic pancreatic carcinoma in a perigastric lymph node. These organisms likely represent carry-through contaminants from the transgastric approach of the endoscopic FNA.